2013
DOI: 10.1063/1.4823812
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Er doping site and concentration on piezoelectric, ferroelectric, and optical properties of ferroelectric Na0.5Bi0.5TiO3

Abstract: The piezoelectric, ferroelectric, and optical properties of Er-doped Na0.5Bi0.5TiO3 ceramics were investigated in terms of Er3+ ion occupying the A- and B-site with different Er ion concentrations. Compared with B-site doped samples, the A-site doped ceramics have much stronger piezoelectricity, ferroelectric property, and luminescence intensity. Upon the excitation of 980 nm, all the Er-doped Na0.5Bi0.5TiO3 ceramics exhibit strong green and red emissions. The present investigation demonstrates that the relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(17 citation statements)
references
References 26 publications
2
15
0
Order By: Relevance
“…ions doping results in decrease of E C . Similar phenomenons were also observed in some literature [16]. With Yb 3?…”
Section: Luminescence Propertiessupporting
confidence: 79%
“…ions doping results in decrease of E C . Similar phenomenons were also observed in some literature [16]. With Yb 3?…”
Section: Luminescence Propertiessupporting
confidence: 79%
“…It has been demonstrated that excellent luminescent performances can be obtained in RE doped ferroelectrics [16][17][18][19]. Moreover, it was also revealed that poling is an effective method to modify the emission intensity of RE doped ferroelectrics [20,21].…”
Section: Introductionmentioning
confidence: 96%
“…Specifically, regarding optical properties it has been observed that some rare earth (RE) elements add additional functionality of light emission in visible spectra to NBT compounds. Zhou et al 9 and recently Luo et al 10 reported a strong green and red emissions in Pr 3þ doped NBT. Furthermore, in Nd 3þ doped NBT crystal, He et al 11 reported a strong absorption around 808 nm that is suitable for AlGaAs diode-laser pumping together with a strong emission around 1.6 lm with long radiation lifetime, which is interesting for application in integrated optoelectronic devices.…”
mentioning
confidence: 98%